PENGARUH LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - Sabaria Suyuti; Sahrullah; Asriani Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The real estate sector in Indonesia faces fluctuations in property values influencedby economic factors, inflation, and government regulations, which can potentiallylead to financial reporting manipulation. This study aims to analyze the effect ofliquidity and firm size on the financial performance of real estate companies listedon the Indonesia Stock Exchange during the period 2020–2023. Using a quantitativeapproach with an associative research method, the study employs purposivesampling and selects 23 companies that meet the criteria of consistent listing,complete annual financial reports, and availability of data relevant to the researchvariables. The variables include liquidity measured by the Current Ratio (CR), firmsize measured by the logarithm of total assets, and financial performance measuredby Return on Assets (ROA). Data were analyzed using multiple linear regressionwith classical assumption tests to ensure model feasibility. The results reveal thatliquidity has a significant positive effect on financial performance, indicating thatfirms with higher liquidity are more capable of fulfilling short-term obligations andimproving profitability. Conversely, firm size has a negative and insignificant effecton financial performance, suggesting that larger firms may face inefficiencies andhigher operational costs that offset their potential advantages. The study concludesthat effective liquidity management is a key determinant of financial performance inthe Indonesian real estate industry, whereas firm size alone does not guaranteesuperior performance. These findings provide practical implications for managersand investors in assessing financial strategies and decision-making within thesector.